Pendaftaran Tanah Wakaf yang Berasal dari Tanah Negara Berdasarkan Peraturan Menteri Agraria dan Tata Ruang No. 02 Tahun 2017 - Jauhari, Muhammad Fikri (Universitas Jember, 2024)
In Islamic law, there is a command known as Waqf. There are organizations that are comparable to waqfs from the standpoint of the Common Law, Anglo-Saxon, and Anglo-American legal systems, specifically charity trusts. When it comes to the purpose, zakat and waqf are similar in that they both aspire to carry out charitable deeds for the good of society. Other religious organizations, such as INFA, zakat and shadaqah distribution institutions, or Badan Amil Zakat, Infaq, and Shadaqah (BAZIS), are one of the rights to control land in addition to other land ownership rights. In theory, these organizations also serve as zakat trustees, with the beneficiaries being specific individuals, the impoverished, and waqf orphans. After that, waqf institutions were recognized and included into Indonesian positive law, namely in the area of agricultural law. The purpose of this research is to serve as study material for gaining knowledge about the processes and methods for awarding waqf rights coming from state land. Research methodologies were used to write this paper. normative and legal, as well as in compliance with Minister of Agrarian Regulation Number 02 of 2017, which outlines the process for awarding waqf for State Land.The word